Plant AP180 N-Terminal Homolog Proteins Are Involved in Clathrin-Dependent Endocytosis during Pollen Tube Growth in Arabidopsis thaliana. (22nd February 2019) - Kaneda, Minako; van Oostende-Triplet, Chlo; Chebli, Youssef; Testerink, Christa; Bednarek, Sebastian Y; Geitmann, Anja
Abstract: Polarized cell growth in plants is maintained under the strict control and exquisitely choreographed balance of exocytic and endocytic membrane trafficking. The pollen tube has become a model system for rapid polar growth in which delivery of cell wall material and membrane recycling are controlled by membrane trafficking. Endocytosis plays an important role that is poorly understood. The plant AP180 N-Terminal Homolog (ANTH) proteins are putative homologs of Epsin 1 that recruits clathrin to phosphatidylinositol 4, 5-bisphosphate (PIP2 ) containing membranes to facilitate vesicle budding during endocytosis. Two Arabidopsis ANTH encoded by the genes AtAP180 and AtECA2 are highly expressed in pollen tubes. Pollen tubes from T-DNA inserted knockout mutant lines display significant morphological defects and unique pectin deposition. Fluorescent tagging reveals organization into dynamic foci located at the lateral flanks of the pollen tube. This precisely defined subapical domain coincides which clathrin-mediated endocytosis (CME) and PIP2 localization. Using a liposome-protein binding test, we showed that AtECA2 protein and ANTH domain recombinant proteins have strong affinity to PIP2 and phosphatidic acid containing liposomes in vitro. Taken together these data suggest that Arabidopsis ANTH proteins may play an important role in CME, proper cell wall assembly and morphogenesis.